6x-y=1

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 6x from both sides of the equation.

-y=1-6x

Multiply each term in -y=1-6x by -1

Multiply each term in -y=1-6x by -1.

(-y)⋅-1=1⋅-1+(-6x)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=1⋅-1+(-6x)⋅-1

Multiply y by 1.

y=1⋅-1+(-6x)⋅-1

y=1⋅-1+(-6x)⋅-1

Simplify 1⋅-1+(-6x)⋅-1.

Simplify each term.

Multiply -1 by 1.

y=-1+(-6x)⋅-1

Multiply -1 by -6.

y=-1+6x

y=-1+6x

Reorder -1 and 6x.

y=6x-1

y=6x-1

y=6x-1

y=6x-1

Rewrite in Slope-Intercept Form 6x-y=1